Controlled Synthesis of Ultrathin PtSe2 Nanosheets with Thickness‐Tunable Electrical and Magnetoelectrical Properties. Issue 1 (28th October 2021) - Ma, Huifang; Qian, Qi; Qin, Biao; Wan, Zhong; Wu, Ruixia; Zhao, Bei; Zhang, Hongmei; Zhang, Zucheng; Li, Jia; Zhang, Zhengwei; Li, Bo; Wang, Lin; et al.
Abstract: Thickness‐dependent chemical and physical properties have gained tremendous interest since the emergence of two‐dimensional (2D) materials. Despite attractive prospects, the thickness‐controlled synthesis of ultrathin nanosheets remains an outstanding challenge. Here, a chemical vapor deposition (CVD) route is reported to controllably synthesize high‐quality PtSe2 nanosheets with tunable thickness and explore their thickness‐dependent electronic and magnetotransport properties. Raman spectroscopic studies demonstrate all Eg, A 1 g, A 2 u, and Eu modes are red shift in thicker nanosheets. Electrical measurements demonstrate the 1.7 nm thick nanosheet is a semiconductor with room temperature field‐effect mobility of 66 cm 2 V −1 s −1 and on/off ratio of 10 6 . The 2.3–3.8 nm thick nanosheets show slightly gated modulation with high field‐effect mobility up to 324 cm 2 V −1 s −1 at room‐temperature. When the thickness is over 3.8 nm, the nanosheets show metallic behavior with conductivity and breakdown current density up to 6.8 × 10 5 S m –1 and 6.9 × 10 7 A cm −2, respectively. Interestingly, magnetoresistance (MR) studies reveal magnetic orders exist in this intrinsically non‐magnetic material system, as manifested by the thickness‐dependent Kondo effect, where both metal to insulator transition and negative MR appear upon cooling. Together, these studies suggest that PtSe2 is an intriguing system for both developing novel functional electronics and conducting fundamental 2D magnetism study. Abstract : Ultrathin 2D PtSe2 nanosheets with various thickness are synthesized by a CVD method. The thickness dependent electrical and magnetoelectrical properties suggest that PtSe2 is an intriguing platform for both developing novel functional electronics and conducting fundamental 2D magnetism studies. The existence of magnetic order in this intrinsically non‐magnetic system will define a new class of magnetic material and stimulate further study.